Analysis of Sweet Corn Farmers' Satisfaction Levels With The Performance of Agricultural Extension Workers in Giripurno Village, Bumiaji District, Batu City - Maslianti, Titi; Gunawan, Cakti Indra; Farah Mutiara (International Research & Development for Human Beings (IRDH), 2025)
Indonesia, as the world's largest archipelagic country located on the equator, has a significant economy, primarily through the agricultural sector. To increase agricultural yields, efforts are needed to improve the quality of human resources, particularly farmers, one of which is through extension activities. This study aims to determine the level of satisfaction of sweet corn farmers with the performance of agricultural extension services in Giripurno Village, Bumiaji District, Batu City. This study employed a descriptive quantitative approach using a Likert Scale and Importance Performance Analysis (IPA). The results indicate that farmer satisfaction is very high and that extension services play a significant role in agricultural businesses. However, extension workers still need to improve the quality of service and program effectiveness so that all farmers can optimally benefit.